EMOTIONAL MATURITY OF HIGHER SECONDARY SCHOOL STUDENTS OF ERNAKULAM DISTRICT, KERALA - TES THOMAS * and LIZMITHA GODWIN, (The Journal of Research ANGRAU, 2022)
The study aimed to analyze the emotional maturity of higher secondary school students inKerala. Using a simple random sampling, 100 adolescents between the age of 16 and 17 yearsfrom five higher secondary schools situated in the Ernakulam district of Kerala were selected forthe study. The data was collected from December 2021 to March 2022. The standardized emotionalmaturity scale developed by Dr. Yashvir Singh and Dr. Mahesh Bhargava (1990) was used tocollect the data. The results indicated that nearly fifty per cent of the students (41%) were in thecondition of ‘extremely unstable’. The difference between girls and boys in the level of emotionalmaturity was not significant, but girls showed higher emotional maturity than boys. Adolescentsfrom rural areas showed higher emotional maturity than adolescents from urban areas, and thedifference was significant concerning, emotional regression, social maladjustment, personalitydisintegration and lack of independence. Further, it is found that emotional instability, regression,social maladjustment, personality disintegration and lack of independence are positively correlatedwith each other.